Localization and distribution of nitric oxide synthase and other neuronal markers in the podia of Holothuria arguinensis. Issue 3 (9th September 2020) - Marquet, Nathalie; Canário, Adelino V. M.; Power, Deborah M.
Abstract: The organization of the nervous system of the holothurian podia—the tentacles, papillae, and tube feet—is still poorly understood, which limits the development of functional studies. Knowledge of nitric oxide (NO) signaling in sea cucumbers is nonexistent, although it is known to play an important role in many essential biological functions, including neurotransmission, throughout the animal kingdom. The objective of this study was to characterize the holothurian podia in Holothuria arguinensis . To this end, we used classical histology, nitric oxide synthase (NOS) distribution, using NADPH‐diaphorase histochemistry and NOS immunostaining, and neuronal immunohistochemistry. Our results revealed an abundant distribution of NO in the nervous components of the holothurian podia, suggesting an important role for NO as a neuronal messenger in these structures. Nitrergic fibers were intensely labeled in the longitudinal nerve and the nerve plexus surrounding the stem, but were more weakly labeled in the mesothelium. NOS was also found in scattered cell bodies and abundant fibers in the podia terminal end (i.e., the discs in tentacles and tube feet, and the pointed conical structures in the papillae), with evident neuronal projections to the bud surface, especially in the tentacles. The podia terminal end was the most specialized area and was characterized by a specific nervous arrangement, consisting of a distinct nerve plate, rich in cells and fibers containing potential sensory cells staining positively for neuronal markers, which makes this the most likely candidate to be a chemosensory region and an important candidate for future exploration.